Understanding Deixis In The Song Lyrics Of Salam Alaikum - Purba, Rafika (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
The researcher selected this song as subject of analysis because the popularity of the song and also it consisted of such as deictic words and reference meaning. Therefore, the Salam Alaikum song lyrics can be analyzed using pragmatics approach. This study was conducted by using descriptive qualitative method. The data which used song lyrics of Harris J’s Salam Alaikum (2015). In addition, this song was classified into three types of deixis analysis based on their own criteria. The result of this research showed that the three types of deixis, there are person deixis, spatial deixis and temporal deixis are used in the Salam Album song lyrics of Harris J. The use of personal deixis indicated the participant in this song. While, the spatial deixis indicated location and place of event from the participant. Moreover, the temporal deixis indicated the timing of speech event which is used in this song.In addition, the most dominant deixis is person deixis. Because, it tells about the moral value, speakers’ experiences and feelings in his religious life.